2022
DOI: 10.1097/ijg.0000000000002160
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Primary Open Angle, Angle Closure, and Normal Tension Glaucoma in an Asian Population Using Optical Coherence Tomography

Abstract: Précis: Spectral-domain optical coherence tomography (SD-OCT) facilitates early glaucoma detection in the Chinese population in Taiwan. The best parameters for primary open angle glaucoma (POAG), primary angle closure glaucoma (PACG), normal tension glaucoma (NTG), and suspected glaucoma (GS) detection are temporal inferior Bruch's membrane opening-minimum rim width (BMO-MRW), inner temporal macular ganglion cell layer (mGCL), temporal superior Circumpapillary retinal nerve fiber layer (cpRNFL), and mean globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(78 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown that OCT can detect glaucomatous defects [4,[13][14] . Consistent with previous studies, we found that the RNFL and GCA thickness decreased with the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that OCT can detect glaucomatous defects [4,[13][14] . Consistent with previous studies, we found that the RNFL and GCA thickness decreased with the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although different pathways are responsible for the development of glaucoma, importance of vascular pathway has been emphasized in recent years [2][3] . Optical coherence tomography (OCT) is a noninvasive method in the detection of early glaucomatous structural damage [4] . Retinal nerve fiber layer (RNFL) and ganglion cell analysis (GCA) have similar accurate diagnostic capacities [5][6] .…”
mentioning
confidence: 99%